The Application of Blockchain Technology in Cross-Border Personal Data Transfer Activities in Indonesia: Opportunities and Challenges - Wijaya, I Made Marta (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 14 No 1 (2025), 2025)
This research seeks to explain the opportunities and obstacles involved in utilizing blockchain technology for transferring personal data beyond Indonesia's legal boundaries, along with the advantages it offers to Personal Data Subjects. The research employs normative legal research with statute and conceptual approaches. Data was collected through document studies and interviews with experts and practitioners, and then analyzed descriptively qualitatively. The findings indicate that blockchain technology has the potential to improve the security, transparency, and efficiency of personal data transfers. Notable opportunities include decentralization features, traceable audit trails, and enhanced identity management solutions. However, challenges such as compliance with varying regulations, data localization, and privacy issues need to be addressed. The study concludes that the application of blockchain technology can provide significant benefits for Personal Data Subjects, offering better data protection and control, along with the fulfillment of rights under Law No. 27 of 2022. A holistic approach and supportive regulations are essential to maximize this technology's potential in cross-border data transfers.